The exercise addiction inventory: a quick and easy screening tool for health practitioners. Issue 6 (23rd May 2005) - Griffiths, M D; Szabo, A; Terry, A
Abstract : Background: Exercise addiction is not routinely screened for probably because available instruments take a long time to administer, their scoring may be complicated, and their interpretation is not always obvious. A new psychometric instrument has been developed that is capable of identifying people affected by, or at risk of, exercise addiction: the exercise addiction inventory (EAI). A preliminary report showed the EAI had good reliability and validity. Objectives: To test further the EAI's psychometric properties and show that it would be quick and simple to administer by general practitioners. Methods: A sample of 200 habitual exercisers were given the EAI and two existing exercise addiction scales (obligatory exercise questionnaire; exercise dependence scale). Two weeks later, another sample of 79 exercisers were administered the EAI to determine the test-retest reliability of the questionnaire. Results: The original data from the preliminary report were reanalysed to determine the split half correlation of the EAI. This was found to be 0.84 (Guttman split-half coefficient). A correlation between weekly frequency of exercising and EAI scores was also determined, and it was found that the two variables shared 29% of the variance ( r 2 = 0.29). The test-retest reliability of the scale was found to be very good (0.85). Conclusions: The EAI is a valid and reliable tool which would be capable of helping general practitioners to quickly and easily identify people affected by, or at risk of, exercise addiction.